Comparison of Indonesian and Malaysian Laws on Prohibition of Monopolistic Practices and Business Competition - Sitepu, Editama Joremia; Marbun, Putra Hasian; Nainggolan, Doni Fernando; Anggusti, Martono (Golden Ratio of Data in Summary, 2025)
Monopolistic practices and unfair competition are significant issues in the global economy. Indonesia and Malaysia have legal frameworks that aim to maintain fair competition and prohibit monopolistic practices. This article compares Indonesian and Malaysian laws prohibiting monopolistic practices and unfair business competition by examining the legal basis, supervision, enforcement mechanisms, and protection of consumers and businesses. Although both countries have similar objectives in protecting market competition, there are differences in the approach to law enforcement, merger and acquisition regulations, and philosophy in competition regulation. The results show that Indonesia focuses more on protecting consumers and small businesses, while Malaysia tends to pay more attention to overall market efficiency.